2001
DOI: 10.1038/86554
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal ceroid depletion by drugs: Therapeutic implications for a hereditary neurodegenerative disease of childhood

Abstract: Neuronal ceroid lipofuscinoses (NCLs) are the most common hereditary neurodegenerative diseases of childhood. The infantile form, INCL, is caused by lysosomal palmitoyl-protein thioesterase (PPT) deficiency, which impairs the cleavage of thioester linkages in palmitoylated proteins, preventing their hydrolysis by lysosomal proteinases. Consequent accumulation of these lipid-modified proteins (constituents of ceroid) in lysosomes leads to INCL. Because thioester linkages are susceptible to nucleophilic attack, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
1
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 40 publications
3
55
1
4
Order By: Relevance
“…Cysteamine bitartrate (Cystagon), a lysosomotropic agent, has been shown in vitro to inhibit the formation of cysteine thioesters, the storage material in PPT1 deficient cells (Zhang et al 2001). It was thus suggested that Cystagon might be used as a substrate reduction agent in infantile NCL due to CLN1 mutations (Zhang et al 2001). This effect on substrate accumulation was not replicated in later experiments (Lu and Hofmann 2006).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Cysteamine bitartrate (Cystagon), a lysosomotropic agent, has been shown in vitro to inhibit the formation of cysteine thioesters, the storage material in PPT1 deficient cells (Zhang et al 2001). It was thus suggested that Cystagon might be used as a substrate reduction agent in infantile NCL due to CLN1 mutations (Zhang et al 2001). This effect on substrate accumulation was not replicated in later experiments (Lu and Hofmann 2006).…”
Section: Introductionmentioning
confidence: 90%
“…The cysteamine bitartrate (Cystagon) was shown to be able to metabolize the storage material in INCL. Study of phosphocysteamine, an agent with very similar structure and activity to Cystagon, was shown to prevent accumulation of storage material and to inhibit apoptosis in lymphoblasts of INCL patients (Zhang et al 2001). However, later in vitro experiments with cysteamine showed inefficient cleavage of PTT substrates by this agent and by related aminothiols (Lu and Hofmann 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When lysosomes cannot recycle/degrade efficiently, an excess storage of various molecules within the cells is created. This abnormal accumulation of undigested material within neurons can lead to cell death (Zhang et al, 2001). In particular, there is evidence that abnormal ceramide metabolism in relation to aberrant lysosomal function can cause neurodegenerative diseases (DitarantoDesimone et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A substrate depletion strategy employing the drug cysteamine has shown promise in cell culture experiments. 12 Cysteamine has a relatively long history for treatment of the lysosomal storage disorder cystinosis and can be tested expeditiously in mice and in humans with the infantile form of NCL. Enzyme replacement therapy (for CLN1 and CLN2 disease) and gene therapy experiments for several of these NCLs are underway.…”
mentioning
confidence: 99%